Optimal licensing strategy of green technology with corporate social responsibility - Li, Dongdong; Shang, Chengxuan; Jiao, Chen (Technological and Economic Development of Economy, 2022)
This study investigates the green technology licensing strategies of firms with corporate social responsibility (CSR) in a duopoly market. The results show that in the absence of CSR, the optimal licensing contract is fixed-fee licensing for a patent holding firm. In the precent of CSR, the optimal licensing contract for a patent holding firm switches from fixed-fee licensing to royalty licensing with increasing level of CSR if the reduction cost of emissions is high. Moreover, we show that the profit goal of firm and the social welfare goal of government are not always mutually exclusive. If the level of CSR is low, a uniform licensing contract would be preferable. If the level of CSR is high, the optimal licensing contract is inconsistent. Finally, we show that CSR is not always beneficial to the social welfare while CSR benefits the environment. Social welfare benefits from increased CSR degree, but vice versa is true when CSR degree decreases. This research may provide valuable insights into licensing and CSR literature.First published online 19 October 2022